BIOTRANSFORMASI ADIPONITRIL OLEH Bacillus licheniformis BA2 - Ahmad Thontowi; Eko W. Pamuji; Bambang Sunarko (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
Adipic acid represents one of the especial materials which used for the synthesis of nylon 6,6,- is a very important material results from polyamide industry. Adiponitrile biotransformation become adipic acid represent an alternative synthesis besides chemically. The purpose of this research was to determine optimum conditions for Bacillus licheniformis BA2 growth for adiponitrile degradation, and also know its pattern. The obtained information, to be expected can be used as reference for scaling up of adipic acid production. B. licheniformis BA2 was able to utilize acetonitrile and adiponitrile as the sole source of carbon and nitrogen. The growth on adiponitrile 120 mM mixture with acetonitrile 30 mM gave higher growth rate and biomass yield than growth on another subsrates. B. licheniformis BA2 have lag phase during 68 hours, logaritmic phase passed by during 104 hours, while stasioner phase just reached by after 172 hours. High-performance liquid chromatography of adiponitrile degradation by crude bacterial revealed a decrease in adiponitrile with the sequential formation of adipamide and adipic acid. Ammonia was also detected by colorimetric procedures. As for adipic acid rendemen at 420 minutes equal to 19.35%.